High‐Efficiency Interdigitated Back Contact Silicon Solar Cells with Front Floating Emitter. Issue 23 (16th October 2019) - Ding, Don; Lin, Hao; Liu, Hong; Lu, Guilin; Li, Zhengping; Zhang, Yueheng; Shen, Wenzhong
Abstract : Silicon interdigitated back contact (IBC) solar cells with front floating emitter (FFE‐IBC) put forward a new carrier transport concept of "pumping effect" for minority carriers compared with traditional IBC solar cells with front surface field (FSF‐IBC). Herein, high‐performance FFE‐IBC solar cells are achieved theoretically combining superior crystalline silicon quality, front surface passivation, and shallow groove structure using 2D device model. The improvement of minority carrier transport capacity is realized in the conductive FFE layer through optimizing the doping concentration and junction depth. It is shown that the shallow groove on the rear side of FFE‐IBC solar cells can effectively enhance the carrier collection ability by means of minimizing the negative impact of undiffused gap or surface p–n junction. The high efficiency exceeding 25% can be realized on silicon FFE‐IBC solar cells with the novel cell structure and optimized cell parameters, where the back surface field and emitter region width can be made for the same with only a slight sacrifice of photocurrent density and conversion efficiency. It is demonstrated theoretically that the realization of high‐efficiency and low‐cost silicon IBC solar cells is feasible due to the increase of the module fabrication tolerance. Abstract : Minority‐carrier transport and collection capacity can be improved, respectively, by the front conductive front floating emitter (FFE) layer and rear shallow groove. Conversion efficiency over 25% on interdigitated back contact silicon solar cells with FFE is achieved, where the back surface field and emitter region width can be made for the same with only a slight sacrifice of photocurrent.